2014
DOI: 10.5798/diclemedj.0921.2014.01.0367
|View full text |Cite
|
Sign up to set email alerts
|

The effects of internet use intensity on quality of life, anxiety and depression scores in pediatric migraine

Abstract: Migren tanısı ile takipli okul çocuğu ve ergenlerin internet kullanım sıklığına göre yaşam kalite indeksi, anksiyete ve depresyon skorlarının, sağlıklı çocuklarla karşılaştırılması amaçlanmıştır.Yöntemler: 9-17 yaş arasında, migren tanısı alan 142 hasta ile aynı yaş ve cinsiyetteki 128 sağlıklı çocuk çalışmaya alındı. Hastaların öykü, öz ve soy geçmiş ve antropometrik ölçümleri de içeren fizik muayene bulguları kaydedildi. Hastalar ergen (˃12 yaş) ve ergen öncesi (<12 yaş) olarak gruplandırıldı. Her yaş grubu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In the present study, students with poor sleep quality were more likely to have migraines; in addition, sleep quality exhibited a dose-response relationship with the prevalence of migraine. This finding is concordant with those of studies reporting that stress and poor sleep are migraine triggers [11,14] . Sleep disturbance is also more common in migraine patients [42] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, students with poor sleep quality were more likely to have migraines; in addition, sleep quality exhibited a dose-response relationship with the prevalence of migraine. This finding is concordant with those of studies reporting that stress and poor sleep are migraine triggers [11,14] . Sleep disturbance is also more common in migraine patients [42] .…”
Section: Discussionsupporting
confidence: 91%
“…They are also prone to both depression and anxiety [9] .Furthermore, a high percentage of medical students suffering from migraines do not seek professional help; rather, they self-medicate. This approach is not ideal, as they may actually be aggravating their migraines [10] .Many studies have also shown that migraines are associated with unhealthy lifestyle choices, including sleeplessness [10,11] , smoking [12,13] , unhealthy snacking [11] , and high computer use [14] . Other work has shown that either obesity or being underweight [15] ,being female [12 ] ,and/or chronic rhinitis [16] may also increase the risk for migraines.…”
Section: Introductionmentioning
confidence: 99%
“…This intense anxiety can cause sufferers to push daily necessities into the background and to experience loss of functionality in many areas of life and a decrease in their QOL . This situation also can cause depression, anxiety, social isolation, sleep problems, psychosocial, and emotional problems . In the current study, the participants who accessed the internet to obtain information at least eight times a day and who did not share the pregnancy‐related information they obtained from the internet with the health professionals had higher trait and state anxiety scores and lower QOL scores.…”
Section: Discussionmentioning
confidence: 62%
“…Trigger factor for children [23] is highly similar to the trigger factor in adults [24] (See Figure 8 & Figure 9). Even the Internet could be one of the trigger factors as Emel Torun et al, [25] found that the misuse of internet in adolescents with migraine might lead to emotional and psychosocial impairment.…”
Section: Try To Detect the Trigger Factor For Your Patientmentioning
confidence: 99%